2007
DOI: 10.1111/j.1532-849x.2007.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

A Technique to Obtain Stable Centric Occlusion Records Using Impression Plaster

Abstract: Recording the maxillomandibular relationship is often a challenge. In situations where there is vertical support but no horizontal stability, and the space between posterior teeth of opposing jaws is not adequate for an interocclusal record, impression plaster can be used. Despite limited clinical use, impression plaster is known for its stability. With this technique, the interocclusal record is obtained by applying the material to the buccal surfaces of the posterior teeth, resulting in a precise and stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Impression plaster has been found to be acceptable for interocclusal registrations by many investigators in the past 10,11,17,18 . They found that the material was accurate, rigid after setting and do not distort with extended storage.…”
Section: Discussionmentioning
confidence: 99%
“…Impression plaster has been found to be acceptable for interocclusal registrations by many investigators in the past 10,11,17,18 . They found that the material was accurate, rigid after setting and do not distort with extended storage.…”
Section: Discussionmentioning
confidence: 99%
“…The interocclusal record is verifiable. 9 Earlier, many studies were conducted to check and correlate various techniques employed in recording the interocclusal records. However, there is a scarcity of literature which explains and compares the material aspect.…”
Section: Issn: 2320-5407mentioning
confidence: 99%